Herbal Monographs and Role of Physalis angulata in Indigenous Herbal Systems: A Literature Review - Subagio, Jonsen (Eduvest - Journal of Universal Studies, 2025)
Physalis angulata L. is an edible and annual herb of the Solanaceae family, known in Indonesia as Ciplukan plant. The fruit which is widely known internationally as Groundcherry is widely consumed by Indonesian people because it has quite high nutritional content and a very delicious taste. In its application in the world of herbal medicine, Physalis angulata L. contains many bioactive compounds which are useful as antifungal, antioxidant, anti-inflammatory, etc. Not only in Indonesia, research related to the herbal application of Physalis angulata L. was also carried out by researchers in a number of tropical and subtropical countries such as Brazil, Vietnam and America. This article aims to summarize and provide a comprehensive review of the characteristics, contents, and various applications of Physalis angulata L. in traditional and modern medicine. This type of research is a literature review by looking for a series of similar studies related to Physalis angulata L. in the form of reports, original articles, and true experiments. This research is a descriptive analysis research and the sources used come from both national and international journals using published articles from Google Scholar, PubMed, and Elsevier with a publication year range from 2019-2024. It is hoped that this literature review will be able to provide a general overview and be a reference for further research, especially in the context of a deeper understanding of the characteristics, content of bioactive compounds, and benefits of Physalis angulata L. as one of the typical herbal plants in Indonesia.